Protective effect of cardioplegia with poly (ADP-ribose) polymerase-1 inhibitor against myocardial ischemia-reperfusion injury: in vitro study of isolated rat heart model. (February 2013) - Yamazaki, Kazuhiro; Tanaka, Seigo; Sakata, Ryuzo; Miwa, Senri; Oriyanhan, Wnimonk; Takaba, Kiyoaki; Minakata, Kenji; Marui, Akira; Ikeda, Tadashi; Toyokuni, Shinya; Komeda, Masashi; Ueda, Kunihiro
<x xml:space="preserve">Abstract</x> Poly(ADP-ribose) polymerase (PARP)-1 inhibitor has been suggested to attenuate the ischemia-reperfusion injury. We investigated the protective effect of the cardioplegia with a PARP-1 inhibitor, 4-hydoxyquinazoline (4-HQ), against myocardial ischemia-reperfusion injury. Isolated rat hearts were perfused on a Langendorff apparatus and cardioplegically arrested for 90 min by perfusion with St. Thomas' Hospital solution (ST-solution). In the Group ST (n = 8), the hearts were arrested with the ST-solution alone. The Group HQ (n = 8) were treated with the ST-solution containing 4-HQ (10 µM) for cardioplegia. During reperfusion, the Group HQ showed significantly greater functional recovery of +dp/dtmax (p = 0.005) and lower enzymatic leakage (p < 0.01). NAD+ levels were also preserved higher in the Group HQ (p < 0.01). Immunohistochemical study revealed lesser extents of oxidative stress and apoptosis, in the Group HQ. Thus, addition of 4-HQ in the cardioplegia may provide a new intervention for myocardial protection against ischemia-reperfusion injury by decreasing NAD+ consumption and suppressing oxidative stress.